Microplastics as emerging atmospheric pollutants: a review and bibliometric analysis - Can-Guven, Emine (SPRINGER, 2021)
Microplastics are ubiquitously present in various environments; thus, they have become a noteworthy issue by researchers. The present study aimed to provide state-of-the-art on microplastic studies and in detail to review the researches on atmospheric microplastic pollution in terms of occurrence, distribution, sampling, analysis, sources, and transport. The results of the bibliometric analysis showed that the annual output in microplastic research has increased, especially during the last 5 years. The research hot spots in the microplastic topic are marine environment, surface water, freshwater, wastewater, toxic effects, and fate and transport of microplastics. The number of studies investigating atmospheric microplastic pollution is still so limited, although microplastics in the atmosphere became one of the notable subjects. Natural and synthetic fibers were mainly detected in the studies investigating microplastic pollution in the air. Textile clothes, anthropogenic activities, and fragmentation of large plastics were indicated as the main sources, while the wind was pointed out as the predominant transport mechanism of atmospheric microplastics. Detailed and comprehensive studies on the determination of the fate and transport of microplastics in the air as well as their health effects are needed.
Keywords: Atmospheric fallout; Fiber; Indoor air; Outdoor air; Research trend; WATER TREATMENT PLANTS; MARINE-ENVIRONMENT; WASTE-WATER; SYNTHETIC-FIBERS; TRANSPORT; ABUNDANCE; SEA; INGESTION; POLLUTION; IMPACTS; Environmental Sciences & Ecology